Thermodynamic models of low-temperature Mn–Ni–Si precipitation in reactor pressure vessel steels. (15th August 2014) - Xiong, Wei; Ke, Huibin; Krishnamurthy, Ramanathan; Wells, Peter; Barnard, Leland; Odette, G. Robert; Morgan, Dane
Abstract